The man from Beijing [videorecording (DVD)] = Der Chinese - Keglevic, Peter, 1950-; Borsody, Suzanne von, 1957-; Nyqvist, Michael, 1960-2017; Michelsen, Claudia, 1969-; Cheng, Amy J. (Amy Jewel), 1970-; Taenaka, Jimmy; Mankell, Henning, 1948-2015 (Music Box Films, 2012)
A search for a killer spanning three continents and three centuries. Based on the international bestselling novel by Henning Mankell, The man from Beijing is a two-part thriller that begins with the stunning murder of 19 people. The only clue left behind is a red ribbon. When Judge Brigitta Roslin discovers that almost all the victims were related to her, she starts an investigation of her own. Her search for the killer leads her to China, where she is confronted with the gruesome machinations of a millionaire businessman.--Container